Chemotactic factor produced by Candida albicans. - Cutler, J E (1977)
Candida albicans was found to produce a substance that was chemotactically active for guinea pig polymorphonuclear neutrophils. The chemotactic factor was detected in culture filtrates of organisms grown under aeration and incubated at 37 degrees C for at least 12 h. Nutrients found to be essential for the production of chemotactic factor included glucose, yeast extract, and a mixture of amino acids. Several strains of C. albicans isolated from humans were tested, and varying degrees of chemotactic activity were found to be associated with the culture filtrates. Only one of the eight isolates did not produce a measurable amount of chemotactic activity. Culture filtrates remained chemotactically active after several cycles of freezing and thawing and after heating at 90 degrees C for 10 min. Substantial evidence is presented that the chemotactic activity is not dependent upon activation of complement.